The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1200/jco.18.00313
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Treatment-Related Cardiotoxicity and Its Impact on Outcomes Among Children Treated in the AAML0531 Clinical Trial: A Report From the Children’s Oncology Group

Abstract: Purpose Late cardiotoxicity after pediatric acute myeloid leukemia therapy causes substantial morbidity and mortality. The impact of early-onset cardiotoxicity on treatment outcomes is less well understood. Thus, we evaluated the risk factors for incident early cardiotoxicity and the impacts of cardiotoxicity on event-free survival (EFS) and overall survival (OS). Methods Cardiotoxicity was ascertained through adverse event monitoring over the course of follow-up among 1,022 pediatric patients with acute myelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
70
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 32 publications
8
70
0
1
Order By: Relevance
“…Overall, there was modest (54%) adherence to protocolmandated echocardiographic evaluations, and the rates were lowest during off-protocol follow-up. 32 As such, the rate of LVSD reported in this study underestimates the true magnitude of risk that may not become apparent until these children enter adulthood. In fact, studies have consistently shown that the echocardiogram obtained in the year after completion of therapy is the most important predictor of future heart failure risk.…”
Section: Secondary Preventionmentioning
confidence: 63%
See 1 more Smart Citation
“…Overall, there was modest (54%) adherence to protocolmandated echocardiographic evaluations, and the rates were lowest during off-protocol follow-up. 32 As such, the rate of LVSD reported in this study underestimates the true magnitude of risk that may not become apparent until these children enter adulthood. In fact, studies have consistently shown that the echocardiogram obtained in the year after completion of therapy is the most important predictor of future heart failure risk.…”
Section: Secondary Preventionmentioning
confidence: 63%
“…The study that accompanies this article by Getz et al 32 describes the incidence and natural history of LVSD in 1,022 pediatric patients with AML treated in the Children's Oncology Group trial AAML0531 (ClinicalTrials.gov identifier: NCT00372593) and examines the effect of LVSD on their EFS and OS. In the study, approximately 12% of patients developed LVSD over a 5-year follow-up, with greater than 70% of incident events occurring during onprotocol therapy (8% incidence of cardiotoxicity while on protocol).…”
Section: Summary Of the Relevant Literaturementioning
confidence: 99%
“…In fact, for at least the past two decades, anthracycline-induced HF has been a leading co-morbidity in survivors of childhood cancers [40]. In 1022 children with acute myeloid leukemia treated in the Children's Oncology Group trial, 12% experienced cardiotoxicity (grade 2 or higher LV systolic dysfunction) during 5 years of follow-up, with more than 70% of incident events occurring during onprotocol therapy [41]. Both event-free survival (hazard ratio [HR], 1.6, 95% CI, 1.2 to 2.1; P = 0.004) and overall survival (HR, 1.6; 95% CI, 1.2 to 2.2; P = 0.005) were significantly worse in patients with documented cardiotoxicity (defined in this study as resting SF < 24% or EF < 50%).…”
Section: Anthracycline-induced Cardiotoxicitymentioning
confidence: 99%
“…Doxorubicin is perhaps the most important agent for the treatment of OS [3]. Most protocols use cumulative doses of 375-450 mg/m 2 , which can be associated with cardiotoxicity during treatment, as well as long-term cardiovascular morbidity and early mortality [4,5].…”
Section: Introductionmentioning
confidence: 99%